2010
DOI: 10.1007/s10554-010-9591-6
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of tissue Doppler imaging in predicting myocardial iron load in patients with beta-thalassemia major: correlation with T2* cardiovascular magnetic resonance

Abstract: Tissue Doppler imaging (TDI) can detect myocardial dysfunction related to iron load in patients with beta-thalassemia major (TM). We aimed to assess the efficacy of pulsed-wave TDI (PW-TDI) in predicting myocardial iron load in patients with TM using T2* magnetic resonance (MR) as the gold-standard non-invasive diagnostic test. 33 asymptomatic TM patients, mean aged 18 +/- 6 years (6-31) with normal left ventricular (LV) global systolic function were evaluated by conventional echocardiography and PW-TDI. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…In those studies, a significant increase in the LV diameters (LV end-diastolic diameter and LV end-systolic diameter) was detected in thalassemia patients relative to the normal control group (26,27). Our findings are in accordance with these studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In those studies, a significant increase in the LV diameters (LV end-diastolic diameter and LV end-systolic diameter) was detected in thalassemia patients relative to the normal control group (26,27). Our findings are in accordance with these studies.…”
Section: Discussionsupporting
confidence: 92%
“…We detected an inverse correlation between the myocardial T2* value and both LVESVi and LVEDVi. The increase in the left ventricular volume or diameter in these patients is mainly attributed to the high cardiac output state secondary to chronic anemia (26). The increase in the left ventricular end-systolic volume has been previously considered a precursor of subclinical left ventricular dysfunction (28).…”
Section: Discussionmentioning
confidence: 99%
“…Also in the literature, reports on diastolic dysfunction in patients with iron overload are conflicting. Indeed some studies using echocardiography [21,22,24,31,32], reported alterations of E/A ratio and E/e'ratios in multiple transfused patients when iron overload by T2* was present. On the other hand, Leonardi et al [16] reported, similar to our findings, poor correlation between various diastolic parameters by echocardiography and T2* measurement by CMR in patients with iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of these studies have demonstrated a significant correlation (25)(26)(27), others have not (11,28). The main limitation of TDI parameters is their dependence on heart rate.…”
Section: Discussionmentioning
confidence: 99%